73.5k views
1 vote
F(1)=-12, f(n)=2f(n-1)
find first 4 terms

User Shumii
by
4.9k points

1 Answer

4 votes

First four terms are: -12, -24, -48, -96

============================================

Step-by-step explanation:

The notation f(1) = -12 tells us that the first term is -12.

The equation f(n) = 2*f(n-1) indicates that we're multiplying the (n-1)th term by 2 to get the nth term. Basically we multiply each term by 2 to get the next term.

-12*2 = -24

-24*2 = -48

-48*2 = -96

So the first four terms are -12, -24, -48, -96.

-----------------------------------

Alternative Approach

f(1) = -12 .... first term

f(n) = 2*f(n-1) ... nth term recursive formula

f(2) = 2*f(2-1) ... plug in n = 2

f(2) = 2*f(1)

f(2) = 2*(-12) ... plug in f(1) = -12

f(2) = -24 ... second term

f(n) = 2*f(n-1) .... resetting for the next computation

f(3) = 2*f(3-1) ... plug in n = 3

f(3) = 2*f(2)

f(3) = 2*(-24) ... plug in f(2) = -24

f(3) = -48 .... third term

f(n) = 2*f(n-1) ... one more reset

f(4) = 2*f(4-1) .... plug in n = 4

f(4) = 2*f(3)

f(4) = 2*(-48) ... plug in f(3) = -48

f(4) = -96 ... fourth term

We get the first four terms to be -12, -24, -48, -96, which was the same as earlier.

User Naresh Babu
by
5.6k points